Designing a Robotic Exoskeleton for Shoulder Complex Rehabilitation - Ball, Stephen J.; Brown, Ian; Scott, Stephen H. (CMBES Proceedings, 2007)
Frequent and repetitive functional training of the upper limb is a key aspect of regaining independence after stroke. Traditionally, this is achieved through manual one-on-one therapy, but patients are often unable to get sufficient treatment due to budget and scheduling constraints. An ideal solution may be robotic therapy, which is becoming an increasingly viable tool. Unfortunately, current rehabilitation robots ignore shoulder girdle motion, even though it plays a critical role in stabilizing and orienting the upper limb during everyday movements. To address this issue, a new adjustable robotic exoskeleton is proposed that provides independent control of six degrees of freedom of the upper limb: two at the sternoclavicular joint, three at the glenohumeral joint and one at the elbow. Its joint axes are optimally arranged to mimic natural upper-limb range of motion without reaching singular configurations and while maximizing manipulability across the workspace. This joint configuration also permits reduction to planar shoulder/elbow motion in any plane by locking all but the last two joints. Electric motors actuate the mechanisms using cable and belt transmissions designed to maximize the load capabilities of the robot while maintaining backdriveability and minimizing inertia. The device will be able to operate both as an assessment tool and as a therapy tool by monitoring and assisting movements. It will also be able to provide any level of gravity compensation. Controlling the entire shoulder complex facilitates training with more natural movements, with the added benefit of gaining the ability to observe and prevent compensatory motion.